THE ROLE OF CULTURE ON ENTREPRENEURIAL BEHAVIOR AND PERFORMANCE OF UMKM TANA TORAJA AND NORTH TORAJA DISTRICTS - Stefani Marina Palimbong; Lisa Kurniasari Wibisono (Jurnal Ekonomi, 2023)
This research aims to analyze the relationship between culture and entrepreneurial behavior on the performance of MSMEs in Tana Toraja and North Toraja Regencies. This type of research uses a quantitative approach, data collection is carried out through questionnaires with a Likert scale. The data analysis technique uses path analysis with SPSS 26 and Sobel Test. The number of respondents in this research was 100 MSME actors. Partially, culture has a significant effect on entrepreneurial behavior, culture has a significant effect on entrepreneurial behavior and culture has an indirect effect on the performance of MSMEs through entrepreneurial behavior in Tana Toraja and North Toraja Regencies.